KUALITAS SENSORIS DAGING PUYUH YANG DIBERI RANSUM SUBSTITUSI TEPUNG IKAN DENGAN TEPUNG MAGGOT (Hermetia illucens): SENSORY QUALITY OF QUAIL MEAT WHICH WERE FED MAGGOT (Hermetia illucens) MEAL AS A SUBSTITUTE FOR FISH MEAL - Fadilla, Audry; Sudrajat, Deden; Wahyuni, Dewi; Kardaya, Dede; Anggraeni (Universitas Djuanda, 2023)
Protein plays an important role in growth. The protein source that is often used is fish meal. The difficult availability of fish meal makes the price expensive, so an alternative is needed to replace fish meal, namely maggot meal. This research aimed to test the effect of substituting fish meal for maggot meal in feed on the sensory quality of quail meat. This research was carried out for 30 days in the poultry house of the Djuanda University livestock study program. 60 quail aged 7 days were used in this study. The design used was a completely randomized design with 5 treatments and 4 replications. The treatment is R0 = 0% maggot meal + 16% fish meal in the ration. R1 = 4% maggot meal + 12% fish meal in ration, R2 = 8% maggot meal + 8% fish meal in ration, R3 = 12% maggot meal + 4% fish meal in ration, R4 = 16% maggot meal + 0 % fishmeal in ration. Data were analyzed using Kruskall Wallis. The variables observed are the hedonic test and hedonic quality (aroma, colour, taste, tenderness, juiceness). The results of the research on the hedonic test showed that there were real differences in aroma, colour, and juiciness but not significant differences in tenderness and taste. In the hedonic quality test, the results of the analysis showed that there were significant differences in all variables except the colour of quail meat. This research concludes that the substitution of fish meals with maggot meals from 4 to 16% can increase the panellists' preference for quail meat and can improve the sensory quality, especially the tenderness, taste, and juiciness of quail meat. Keywords: hedonic, BSF larva, hedonic quality